Kemampuan Menentukan Unsur Puisi Dengan Berbantuan Media Audio Visual Kelas X SMA Negeri 1 Siberut Selatan - Dwi Muthia Chan; Susanti Marisya; Ria Hillaria Sabolak (Kilau Publishing, 2023)
This study focuses on the low poetry writing skills of tenth-grade students at SMA Negeri 1 Siberut Selatan, Mentawai Islands Regency. The purpose of the research is to describe poetry writing abilities with the aid of audio-visual media. The method used is descriptive quantitative research with random sampling techniques. The data analyzed consists of scores from poetry writing tests. The analysis steps include examining students' writings, assessing them based on a rubric, recording scores, determining average scores, and creating histograms. The results show that students' abilities in the theme and message indicators are categorized as